Isolation of Bacteria from Lead-Contaminated Soil and Bacterial Interaction Test with Plant Growing on Lead-Amended Media - Dian Siswanto; Nurul Istiqomah; Azizuddin Muhammad Nashafi; Mukhaddam Muhammad; Fathul Mukaromah; Irfan Mustafa (Tropical Life Sciences Research, 2025)
The study investigated bacterial isolation from lead-contaminated soil, revealing the lower bacterial density compared to agricultural soil bacteria, indicating soil degradation. Among the isolated bacteria, three isolates with codes L03, L16, and L19 exhibited high tolerance to lead concentrations up to 1,500 mg/L. Selected isolates demonstrated the ability to produce Indole-3-Acetic Acid (IAA) hormone, with one strain notably producing the highest IAA concentration. Furthermore, three isolates exhibited significant lead bioaccumulation efficiency. Molecular identification revealed Lysinibacillus fusiformis as the highest IAA-producing strain and lead accumulator. Plant growth experiments analysed the bacteria's potency to alleviate the heavy metal stress on Codiaeum variegatum, Dracaena reflexa and Jasminum humile. Additionally, bacterial addition decreased lead absorption only by D. reflexa, potentially through biosorption and bioaccumulation mechanisms. Integrating L. fusiformis into phytoremediation strategies could offer an effective and sustainable approach for remediating Pb-contaminated environments.